The use of UTAUT model to understand user intention and user behavior of mobile banking BIMA PT Bank Jateng - Christophorus Bagus Ratnanto Putro; Maria Apsari Sugiat (Goodwood Publishing, 2025)
Purpose: This study aims to explore the factors influencing users’ behavioral intention and actual usage behavior of the BIMA mobile banking application by PT Bank Jateng. It applies the Unified Theory of Acceptance and Use of Technology (UTAUT), enriched with contextual variables including mobile self-efficacy, perceived enjoyment, and user satisfaction. Research/methodology: A quantitative method was adopted through a structured survey of 384 BIMA users. Data were analyzed using Structural Equation Modeling (SEM) via SmartPLS. Validity and reliability were tested using AVE and Composite Reliability, while model fit was assessed through SRMR, NFI, R², and Q² values. Results: Out of 13 hypothesized relationships, 10 were supported. Mobile self-efficacy significantly influenced perceived enjoyment, which in turn strongly affected performance expectancy, effort expectancy, and satisfaction. Consumer satisfaction emerged as the most influential factor affecting intention to use, which subsequently impacted usage behavior. Social influence and facilitating conditions also significantly influenced behavioral outcomes. However, performance expectancy did not significantly influence satisfaction, and both effort expectancy and facilitating conditions showed no significant impact on intention to use. Conclusions: Emotional factors like perceived enjoyment and satisfaction, along with social influences, play a more dominant role than purely functional factors (e.g., effort or performance expectancy) in determining adoption and continued use of mobile banking. The findings suggest a shift from technical-centric to user experience-centric approaches in digital banking development. Limitations: This study focuses solely on the BIMA mobile banking app using a cross-sectional design and PLS-SEM method. It does not account for moderating or mediating variables and may limit generalizability beyond the study context. Contribution: The study extends the UTAUT model by adding emotional and contextual factors to better explain mobile banking usage and offers practical insights for improving user experience and digital adoption in regional banking.